Meeting the challenge of antibiotic resistance. (18th September 2008) - Cars, Otto; Högberg, Liselotte Diaz; Murray, Mary; Nordberg, Olle; Sivaraman, Satya; Lundborg, Cecilia Stålsby; So, Anthony D; Tomson, Göran
Abstract : A concerted global response is needed to tackle rising rates of antibiotic resistance, say Otto Cars and colleagues